Hermeneutics and analogue law. The conception of the law of Michel Bastit (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this article one tries to analyze the complexity of the Law. And MichelBastit´s thought takes as a reference. The different conceptions of the Law positivists, antiformalists, etc.) they arrange and are interpreted depending on a morewide and comprenhensive conception of the Law, this is, a hermeneutics conceptionof the Law. The contemporary hermeneutics, the interpretations of the law and theanalogy will be the steps that drive us to descipher a conception of the Law, that ofBastit, which tries to harmonize the form and the purpose in the Law.
Keywords: Hermeneutics; juridical logic; analogy; conceptions of the law; justice; univocal law; equivocal law; dialectical law.